Strategies to Increase the Motivation of Tahfidz Al-Quran - Phen Anoum; Filza Arifa; Cheen May (Journal International Inspire Education Technology, 2022)
Strategy is a structured and planned effort that a person uses to achieve certain goals. Motivation is a positive encouragement that is given by someone to the individual. Tahfidz Al-Quran is a person who is able to memorize verses of the Qur’an from the first juz to the last juz. In memorizing the Qur’an, an appropriate strategy must be used, this strategy will be used by an educator to guide students in memorizing the Qur’an and the strategies used must be in accordance with the abilities of each student. Here the researcher conducts research at the Islamic Boarding School Adlaniyah Modern Ujung Gading, this study aims to find out what strategies are used to increase the motivation of Tahfidz Al-Quran. The technique used by researchers in collecting data or information by means of observation and conducting interviews with one of the tahfidz teachers and several students as well as documentation. The subjects of the study were teachers and students. As for the results of this study, it turns out that educators use different strategies such as repeating verses, memorizing verse sequences, and not moving on to the next verse if the first verse has not been memorized, teachers also use the place method and continue the verse. This makes the students more motivated to memorize the Al-Quran.